2021
DOI: 10.1590/1807-1929/agriambi.v25n6p372-379
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus doses alter the ionic homeostasis of cowpea irrigated with saline water

Abstract: HIGHLIGHTS Irrigation using water with electrical conductivity above 2.5 dS m-1 is not adequate for ‘Paulistinha’ cowpea. Increment in phosphorus dose does not increase phosphorus content in cowpea plant. Under salt stress conditions, cowpea plants require lower doses of phosphorus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
1
5
0
3
Order By: Relevance
“…In the cowpea culture, Sá et al (2021) also observed a quadratic behavior in the concentration of Mg in the area, noting an increase up to the electrical conductivity of the water of 1.34 and 1.10 dS m -1 , with subsequent reductions up to the value of 4.5 dS m -1 .…”
Section: Resultsmentioning
confidence: 86%
“…In the cowpea culture, Sá et al (2021) also observed a quadratic behavior in the concentration of Mg in the area, noting an increase up to the electrical conductivity of the water of 1.34 and 1.10 dS m -1 , with subsequent reductions up to the value of 4.5 dS m -1 .…”
Section: Resultsmentioning
confidence: 86%
“…Thus, decreases in fruit size and weight were not due to poor fertilization and poor fruit formation, which are capable of reducing sink strength (fruit) [ 20 ]. However, the restricted availability of water and photoassimilates due to the osmotic and ionic salinity components limits root development, leaf growth and expansion (source), and water relations and photosynthesis [ 2 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low rainfall and high temperatures characterize the Brazilian semi-arid region for most of the year and high evapotranspiration rates [ 1 ]. Along with these factors, soil salinization is prevalent, causing losses in crop yield and quality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Según Araújo da Silva et al (2014), un elemento como el fósforo influye en el aumento del número de vainas y masa de los granos. Por ello, Sá et al (2021) afirman que solo es necesaria una dosis adecuada de fósforo para minimizar los efectos salinos en el frijol caupí. Ello puede explicar la existencia de un mayor número de semillas y vainas a concentraciones bajas de detergente, a diferencia de las concentraciones altas e, incluso, de la planta testigo, en vista de que el fósforo se encuentra presente en el detergente bajo la forma de fosfato (Araújo da Silva et al, 2014).…”
Section: Discussionunclassified